Propoxyphene and the risk of out‐of‐hospital death. (14th February 2013) - Ray, Wayne A.; Murray, Katherine T.; Kawai, Vivian; Graham, David J.; Cooper, William O.; Hall, Kathi; Michael Stein, Charles
ABSTRACT Purpose The opioid analgesic propoxyphene was withdrawn from the US market in 2010, motivated by concerns regarding fatality in overdose and adverse cardiac effects, including prolongation of the QT interval. These concerns were based on case reports, summary vital statistics, and surrogate endpoint studies. Methods Using the linked Tennessee Medicaid database (1992–2007), we conducted a retrospective cohort study that compared risk of sudden cardiac, medication toxicity, and total out‐of‐hospital death for propoxyphene users with that for comparable nonusers of any prescribed opioid analgesic and users of hydrocodone, an opioid with similar indications. Cohort members had 1 873 500 propoxyphene prescriptions, 1 873 500 matched nonuser control periods, and 936 750 matched hydrocodone prescriptions. Results Current propoxyphene users had no increased risk for sudden cardiac death (versus nonusers: hazard ratio [HR] = 1.00 [0.81–1.23]; versus current hydrocodone users: HR = 0.91 [0.68–1.21]) but did have increased risk for medication toxicity deaths (versus nonusers: HR = 1.85 [1.07–3.19], p = 0.027; versus current hydrocodone users: HR = 2.10 [0.87–5.10], p = 0.100). Because toxicity deaths were a small proportion of study deaths, total out‐of‐hospital mortality differed by less than 10% between the study groups and was not significantly elevated for propoxyphene (versus nonusers: HR = 1.09 [0.95–1.25]; versus current hydrocodone users: HR = 1.06 [0.87–1.29] ). Conclusions Our findings support the concern that propoxyphene has greater toxicity in overdose but do not provide evidence that it increases the risk of sudden cardiac death. Copyright © 2013 John Wiley & Sons, Ltd.